PENGARUH KEMAMPUAN TEKNIK PEMAKAI SISTEM INFORMASI AKUNTANSI DAN KETIDAKPASTIAN TUGAS TERHADAP KINERJA SIA DENGAN PENDIDIKAN DAN PELATIHAN SEBAGAI VARIABEL MODERASI - Ni Putu Meri Yanti; Cokorda Gde Bayu Putra (Hita Akuntansi dan Keuangan, 2021)
Bookkeeping Information Systems will be frameworks that gather, store and cycle monetary and bookkeeping information utilized by chiefs. Bookkeeping data is for the most part a PC based framework and a strategy for following bookkeeping exercises according to data innovation assets. This examination means to decide the impact of the client's specialized capacity, task vulnerability on AIS execution and to decide the directing impact of the client's specialized capacity and assignment vulnerability in instruction and preparing. This examination was led at the LPD North Kuta District. The example in this examination were 85 representatives engaged with the utilization of bookkeeping data frameworks. The testing technique utilized in this investigation was purposive inspecting. The information examination method utilized in this investigation was Smart PLS 3.0. The outcomes showed that the User Technical Ability variable had a positive and huge impact on AIS Performance, Task Uncertainty had a positive and unimportant impact on AIS Performance, Education and Training Interaction with User Technical Ability couldn't reinforce AIS. Execution, yet Education and Training interfaces with Uncertainty Tasks can fortify AIS Performance.